OBSERVATION ON THE TRANSCRIPTION OF THE CLEAR MONGOL SCRIPT’S LONG VOWELS - Ts.Munkhtsetseg (Acta Mongolica, 2014)
The Clear Mongol script was created in 1648 by the Oirat erudite Zaya Pandita Nam-mkha’i rgya-mtsho (1599-1662). The script was largely used by Oirat scholars in their literary composition. However, in spite of its longevity, the use of this script did not expand beyond the inner circle Oirat scholars. Nevertheless, a comprehensive history of the Clear Mongol script would indicate that this script made a substantial contribution to the literacy development of the Mongol people as testified by its use in Buddhist manuscripts, the Buddhist philosophy in the 17th and 18th century as well as in literary composition in general.